G148 Neonatal ECG interpretation: A disappearing art?. (27th April 2016) - Brindley, C; Patel, L; Bhojnagarwala, B
Abstract : Background: The Royal College of Paediatrics and Child Health (RCPCH) list interpretation of basic cardiological investigations as an essential skill in the neonatal curriculum. The authors postulate however that trainees lack confidence in interpretation of the neonatal electrocardiogram (ECG), which is central to the management of newborn babies with heart murmurs, arrhythmias and complex congenital abnormalities. Literature search identifies only one UK study in paediatric ECG interpretation and none for neonatal ECGs. There was therefore a need to evaluate competence amongst clinicians, and identify whether further formal training would be of benefit. Objective: To establish the current level of competency, confidence and need to develop formal training in neonatal ECG interpretation. Design/Methods: Paediatric and neonatal trainees, consultants, nurse practitioners and clinical fellows were surveyed throughout the UK by questionnaire. Confidence and perceived training needs were addressed with 5 initial questions: level of training, perceived confidence interpreting neonatal ECGs, frequency of interpretation, available teaching, and value of further training. A further 10 question quiz assessed current competence with neonatal ECG examples and 5-part multiple choice questions. The survey was distributed nationally through Deanery administrators contacted via the RCPCH. Results were returned via the online system Survey Monkey. Results: 154 responses were received, of whom 102 (66%) also completed the quiz. 121 (78%) rated their confidence in neonatal ECG interpretation as 3 or below out of 5 (5 being most confident); only 2% rated 5. 30% stated they never receive neonatal ECG teaching, with a further 61% only rarely receiving teaching. Only 9% of the 102 answered all the questions correctly: most at ST 7–8 level, all of whom rated their confidence at 3 or 4. Conclusions: Our study is the first, of which the authors are aware, to evaluate nationally competence in neonatal ECG interpretation. Results showed that confidence was rated low amongst trainees throughout all training grades, and the vast majority received no or infrequent dedicated teaching. Our results indicate that development of formal neonatal ECG training would be beneficial and welcomed amongst clinicians, and as an essential skill in neonatal clinical practice, should form a high priority.